Economies of Scale in Multi-Output Production - Panzar, John C.; Willig, Robert D. (Quarterly Journal of Economics, 1977)
I. Introduction, 481.—II. Counterexamples, 482.—III. Economies of scale, 484.—IV. Technological regularity conditions, 487.—V. The profitability of marginal cost pricing, 488.—VI. Concluding remarks, 492.